Answer: No, x+3 is not a factor of 2x^2-2x-12
========================================================
Explanation:
Let p(x) = 2x^2 - 2x - 12
If we divide p(x) over (x-k), then the remainder is p(k). I'm using the remainder theorem. A special case of the remainder theorem is that if p(k) = 0, then x-k is a factor of p(x).
Compare x+3 = x-(-3) to x-k to find that k = -3.
Plug x = -3 into the function
p(x) = 2x^2 - 2x - 12
p(-3) = 2(-3)^2 - 2(-3) - 12
p(-3) = 12
We don't get 0 as a result so x+3 is not a factor of p(x) = 2x^2 - 2x - 12
----------------------------------------
Let's see what happens when we factor p(x)
2x^2 - 2x - 12
2(x^2 - x - 6)
2(x - 3)(x + 2)
The factors here are 2, x-3 and x+2
Yes!! Good job! You’re correct
You divide 30 miles by 10 to get 3 miles, so you do the same for the bottom.
20 hours divided by 10 = 2 hours.
2 hours is the answer.
Your 14 years old and you don’t know how to do it haha
Answer:
Let x = number of gate tickets, ($1.50)
:
Since there were 600 tickets sold, let (600-x) = the $1 tickets
:
1.50 tickets + $1 tickets = $700
:
1.5x + 1(600 - x) = 700
1.5x - x = 700 - 600
.5x = 100
x = 100/.5
x = 200 ea 1.50 tickets sold at the gate
;
;
Check: there were 600 - 200 = 400 ea $1 tickets sold
1.50(200) + 1(400) = $700